PERTUMBUHAN DAN HASIL JENIS UBI BANGGAI (Dioscorea spp) PADA BERBAGAI PUPUK ORGANIK - Nirwan Sahiri, Ichwan Madauna, Yusuf (AGROTEKBIS, 2015)
Banggai yam (Dioscorea spp) has a great potential to be developed as a companion crop of rice. Government policies regarding food diversification and the limited arable land in Sulawesi, will provide a great opportunity in this plant. The research objective was to compare the growth and yield some kind of potato Banggai on aplication of various organic fertilizers. This research was conducted housed in the Village. Tondo, East Palu. The experiment began forFebruari to Agustus 2014. The study was a randomized block design (RAK) with three treatments, namely: no treatment (control), Bokashi (manure of poultry) and ash. Where each treatment was repeated three times resulting in 27 experimental units. Significantly different treatment in further test honestly significant difference test (HSD) level of 5%. Parameter observations on the components of growth include the number of shoots, plant height and to include the results of components, total fresh weight of tubers / plot, tuber number of plants / plot, the diameter of the bulbs. Ubi type Banggai significant effect on the growth of the number of plant height (302.72 cm), the number of shoots (3.20) was obtained on the type Raw Memeila Boan, while data results indicate that the type of Raw Boan Memeila more dominant crops produce the amount of 5.78 plant, tuber number 6.89, and 21.01 cm diameter than the bulb types and kinds of Raw Materials Pusus Tu'u, Giving type of organic fertilizer had no significant effect on growth and yield Ubi Banggai and Banggai interaction between the type of potato and organic fertilizer nor significantly affected the growth and yield of potato Banggai.